2001
DOI: 10.1128/jcm.39.6.2178-2183.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human Babesiosis in Japan: Isolation of Babesia microti -Like Parasites from an Asymptomatic Transfusion Donor and from a Rodent from an Area Where Babesiosis Is Endemic

Abstract: To determine the source of infection for the Japanese index case of human babesiosis, we analyzed blood samples from an asymptomatic individual whose blood had been transfused into the patient. In addition, we surveyed rodents collected from near the donor's residence. Examination by microscopy and PCR failed to detect the parasite in the donor's blood obtained 8 months after the donation of the blood that was transfused. However, we were able to isolate Babesia parasites by inoculating the blood sample into S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
109
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 31 publications
0
109
0
4
Order By: Relevance
“…Detection of B. microti-specific DNA in blood samples: Nested PCR for detection of Babesia parasites in the blood specimens of the field collections was carried out according to the previously published protocol [31,34]. All oligonucleotide primers used for various PCR are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of B. microti-specific DNA in blood samples: Nested PCR for detection of Babesia parasites in the blood specimens of the field collections was carried out according to the previously published protocol [31,34]. All oligonucleotide primers used for various PCR are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous investigations on the first Japanese case of human babesiosis [25,34] proved that the patient was infected by blood transfusion from an asymptomatic carrier. A following epidemiological survey [31] further revealed that two types of B. microti-like parasites, namely Kobe and Hobetsu, are enzootic among Japanese small wild rodents, and that Apodemus speciosus, a species of Muridae unique to Japan, serves as the major reservoir of the agent of human babesiosis.…”
mentioning
confidence: 99%
“…Seemingly identical B. microti-like parasites (designated as the Kobe type) were isolated from both the patient and an asymptomatic carrier who had donated the units of blood that were transfused into the patient. The same type of parasite has also been found in Apodemus mice captured near the donor's residential area [22,23]. More recently, however, we have isolated a number of B. microti-like parasites from wild rodents captured at various places in Japan, and found that another type of parasite (designated as the Hobetsu type), which differs antigenically and genotypically from the Kobe type, is the major type distributed among Japanese small wild rodents [22].…”
mentioning
confidence: 91%
“…Strain Ko524 [19] was isolated from the Japanese index case patient in Kobe City, Hyogo Prefecture, Japan [13]. Strain Ho234 was isolated from a large Japanese field mouse (Apodemus speciosus) captured in Hokkaido [23]. These two Japanese strains were serologically distinct, and were used as the type strains of Kobe-and Hobetsu-type parasites, respectively.…”
Section: Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation